In-flight development of SINS-500NS satellite inertial navigation system at high latitudes - Chernodarov, A. V.; Patrikeev, A. P.; Karpov, O. A. (2018 25th Saint Petersburg International Conference on Integrated Navigation Systems (ICINS), 2018)
Basic features of implementing the modes of operation of a strapdown inertial navigation system (SINS) under polar conditions are considered. The above-mentioned SINS based on fiber-optic gyros has been the subject of our studies. Approaches to the improvement of the accuracy characteristics of such SINS are proposed, which are based on the use of geophysical invariants and on the integrated processing of appropriate observations. The results of field development of the SINS presented in this paper are shown and analyzed.